137k views
0 votes
What is the solution to this system of linear equations? 2x + y = 1 3x – y = –6 (–1, 3) (1, –1) (2, 3) (5, 0)

User Databyte
by
5.5k points

2 Answers

3 votes

Answer:

(-1, 3)

Explanation:

User Anar Bayramov
by
5.9k points
5 votes

Answer:


(-1, 3)

Explanation:

We have two equations:


2x+y=1\\3x-y=-6

Adding the two linear equations:


(2x+3x)+(y-y)=1+(-6)

Simplifying


5x+0y=1-6


5x=-5\\

Clearing for
x:


x=(-5)/(5) \\x=-1

Now we substitute this value of
x in either of the two initial equations to find the value of
y, Substituting in the first one:


2x+y=1\\2(-1)+y=1\\-2+y=1\\y=1+2\\y=3

the answer is
(-1, 3) because
x=-1 and
y=3

User Meda
by
5.9k points